Morbidity among children living around clinical waste treatment and disposal site in the Northwest region of Cameroon - Peter I. K. Mochungong; Gabriel Gulis; Morten Sodemann (AOSIS, 2011)
Clinical waste is ineffectively treated and disposed in Cameroon. Disposal sites have unrestricted access and are located within communities. We hypothesize that vector proliferation and exposure to chronic low-level emissions will increase morbidity in children living around such sites. Self-reported disease frequency questionnaires were used to estimate the frequency of new episodes of intestinal, respiratory and skin infections among exposed children less than 10 years. Data was simultaneously collected for unexposed children of the same age, using the same questionnaire. Data reporting by the parents was done in the first week in each of the 6 months study period. The risk ratios were 3.54 (95% CI, 2.19-5.73), 3.20 (95% CI, 1.34-7.60) and 1.35 (95% CI, 0.75-2.44) for respiratory, intestinal and skin infections respectively. Their respective risk differences were 0.47 (47%), 0.18 (18%) and 0.08 (8%). The study revealed that poor treatment and disposal of clinical waste sites enhance morbidity in children living close to such areas. Simple health promotion and intervention programs such as relocating such sites can significantly reduce morbidity.